(untitled) (Global Journal of Science Frontier Research, 2012)
This study investigated the growth trend of farmers’ groups in Delta State, Nigeria.Primarily data were collected from 77 respondents randomly selected from 20 randomly selected farmers’ groups, while secondary data were collected from 20 randomly selected farmer’s groups records. The Data were measured with the use of frequency counts and percentages, contingent tables and inferential statistics was analyzed with the use of ANOVA. Most of the groups experienced dwindling membership strength and decreased payment of monthly subscription fees. The individual members rarely had access to credit and cheap inputs. There was significant difference in membership strength in the period (2002-2011) under study. Implication for sustainable agricultural production and extension service was emphasized. It was recommended that extension agents should organize leadership training, at regular intervals, for the group leaders; leaders of the various groups should endeavour to disseminate information on any meeting to members adequately and early enough and extension agents should fix their meetings with group members’ participation.